2023
DOI: 10.3390/biomedicines11082153
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pathogenesis and Mechanism-Targeted Treatments of Rosacea: Previous Understanding and Updates

Chengqian Chen,
Peiru Wang,
Linglin Zhang
et al.

Abstract: Rosacea is a chronic inflammatory skin disease characterized by recurrent erythema, flushing, telangiectasia, papules, pustules, and phymatous changes in the central area of the face. Patients with this condition often experience a significant negative impact on their quality of life, self-esteem, and overall well-being. Despite its prevalence, the pathogenesis of rosacea is not yet fully understood. Recent research advances are reshaping our understanding of the underlying mechanisms of rosacea, and treatment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 288 publications
0
5
0
7
Order By: Relevance
“…Recent evidence has pointed to the role of activated B cells, as testified by high levels of B cell markers in skin biopsies of rosacea patients [47]. Additionally, B lymphocytes are responsible for the production of fibrogenic cytokines, such as IL-6 and transforming growth factor beta (TGFb), implicated in the fibrotic changes in phymatous rosacea [8].…”
Section: Immune Dysregulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence has pointed to the role of activated B cells, as testified by high levels of B cell markers in skin biopsies of rosacea patients [47]. Additionally, B lymphocytes are responsible for the production of fibrogenic cytokines, such as IL-6 and transforming growth factor beta (TGFb), implicated in the fibrotic changes in phymatous rosacea [8].…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…Notably, the sebaceous fatty acid profile in patients with rosacea shows a decrease in long-chain saturated fatty acids that leads to skin dryness and hypersensitivity [61]. In this context, sebocytes could contribute to the general inflammatory status by releasing proinflammatory cytokines and adypokines, including IL-6 [8]. Although the pathophysiological link between chronic inflammation and glandular hyperplasia remains elusive, sebaceous gland dysfunction in rosacea might arise from TLR-mediated inflammatory status, changes in the skin microbiome, alteration in neuronal and endocrine factors, and alteration in skin barrier permeability [62].…”
Section: Other Contributors (Sebaceous Glands Skin Barrier Dysfunctio...mentioning
confidence: 99%
See 1 more Smart Citation
“… 70 An over 14-year follow-up study showed that body mass index positively correlates with the risk for rosacea at least in females (p < 0.0001). 71 Because of the pathogenic role of inflammation in both obesity and rosacea, 29 , 72 , 73 management of one condition can benefit the other one. The links of seborrheic dermatitis and bullous pemphigoid to neurological, metabolic and cardiovascular diseases have also been well documented.…”
Section: Association Of the Skin With Aging-associated Conditionsmentioning
confidence: 99%
“…2 The related symptoms of rosacea seriously affect the psychological state of patients. 3 Despite its prevalence, the precise mechanisms underlying Rosacea remain uncertain, with potential links to immune and neurovascular disorders, 4 it may also be related to solar damage 5 and demodex mites. 6 Environmental triggers are also believed to contribute to Rosacea's development and progression.…”
Section: Introductionmentioning
confidence: 99%